ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM PROBIOTIK PADA PT. GUNUNG MAS - Ina Ratnasari; Suhono Suhono; Evi Selvi (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
The business opportunity of probiotic chicken business is very large because currently there are still few breeders who do breeding probiotic chicken while the demand for chicken probiotics along with awareness of people who are increasing in choosing healthy and low cholesterol food products. PT. Gunung Mas plans to expand its business by increasing the probiotic chicken breeding business sector. Before running the plan, PT. Gunung Mas conducted a business feasibility study to be able to decide whether the probiotic chicken breeding business plan is feasible or not to be implemented. Based on the results of research on non-financial aspects of market aspects, marketing aspects, technical aspects and technology, aspects of management and human resources and environmental aspects, probiotic chicken breeding business feasible to be implemented. While the financial aspects of the payback period, net present value, profitability index and internal rate of return, probiotic chicken breeding business feasible to be implemented Keywords : Feasibility studies, probiotic chicken breeding, non financial aspect, financial aspect